Reputasi Sekolah dalam Perspektif Orang Tua Milenial: Studi Kualitatif tentang Faktor-faktor Branding yang Mempengaruhi Keputusan Memilih Sekolah - Junaidi, Junaidi; Karim, Hamdi Abdul (YASIN, 2025)
Although school choice and educational branding have been widely examined, research that specifically investigates how school reputation, digital branding, teacher quality, flagship programs, and social verification interact in millennial parents’ decision-making processes remains relatively limited. This study aimed to explore in depth the mechanisms underlying millennial parents’ considerations when choosing schools for their children by focusing on six key factors: school reputation as an initial filter, digital branding as the shaper of primary perceptions, teacher quality as the basis for substantive evaluation, flagship programs as institutional differentiators, the physical environment as tangible verification, and word of mouth as the final validation. The study employed a qualitative case study design involving 12 participants selected through purposive sampling. Data were collected through in-depth interviews, supporting observations, and a review of digital documentation, and were analyzed using thematic analysis. The findings show that millennial parents’ decisions are shaped by the interaction between symbolic image, digital representations, and empirically verified evidence at the interpersonal level, whereby reputation and digital branding function as triggers of initial perceptions, while teacher quality, flagship programs, and the school environment serve as the ultimate determinants of trust. These results contribute to the development of educational brand equity theory by adding the dimension of digital credibility and provide methodological enrichment by demonstrating the importance of qualitative approaches for understanding the motives and processes underpinning educational decision-making. Practically, the study underscores the need for consistency between digital branding and schools’ actual practices, the strengthening of teachers’ capacity as the primary representatives of the brand, and the optimization of testimonial-based communication strategies. Future research is recommended to test this model quantitatively and to extend its application to different demographic contexts.